Phytochemical constituents from Melicope pteleifolia that promote neurite outgrowth in PC12 cells. (May 2016) - Xu, Jing; Sun, Xiaocong; Liu, Xingyu; Peng, Maoqin; Li, Shen; Jin, Da-Qing; Lee, Dongho; Bartlam, Mark; Guo, Yuanqiang
Highlights: Thirteen compounds were isolated from the stems of Melicope pteleifolia . Their structures were elucidated by analysis of NMR and MS spectroscopic data. Four compounds are new chroman derivatives. Eleven compounds showed promoting effects on neurite outgrowth of PC12 cells. Abstract: Bioactive substances that promote neurite outgrowth and prevent neuronal degeneration are potentially useful for the medical treatment of Alzheimer's disease (AD). This study aimed to obtain bioactive compounds from the stems of the medicinal and edible plant Melicope pteleifolia that promote neurite outgrowth. A bioassay-guided phytochemical investigation led to the isolation of four new chroman derivatives, pteleifolones A–D (1 –4 ), and nine known components, acronyculatin B (5 ), acronylin (6 ), marmesin (7 ), 5-methoxymarmesin (8 ), (+)-peucedanol (9 ), atanine (10 ), N -methylatanine (11 ), dictamnine (12 ), and evolitrine (13 ). Their structures were established by extensive nuclear magnetic resonance (NMR) spectroscopic data analysis. Most of these compounds promoted nerve growth factor (NGF)-mediated neurite outgrowth in PC12 cells. These chemical and biological results provide a basis for the further development and utilization of M. pteleifolia as a functional food.